Estratégias de leitura: processos de compreensão deflagrados por crianças de 5º ano diante do texto escrito - Garcia, Ivete Nunes (2016)
The present research deals with the reading strategies of experienced readers as described by the specialized literature. This subject has a lot of relevance both in academic research and in school since people use reading to gain access to the historically accumulated knowledge, making use of strategies that help them understand what they are reading. The research objectives are: to recognize the reading strategies used by students of a 5th grade when facing a written text; to explore the concept of reading based on authors who deal with the psycholinguistics perspective; to discuss the teaching of reading in the school cont ext in confrontation with the demands coming from external evaluations. For such purposes, a bibliographical study anchored to theoretical references about reading in psycholinguistics was made, based on the studies of Smith (2003), in addition to the contributions of Solé (1998), Kleiman (2013, 2010), Colomer and Camps (2002) and Girotto and Souza (2010). In addition to the theoretical contributions, a qualitative methodology involving observations and interviews based on the clinical method and on verbal protocols was used. The field work was developed in an elementary school, in the North of Rio Grande do Sul, with a 5th grade class. The text is organized into four chapters, besides the introduction and final considerations. The first chapter contains the reflections on the concept of reading; the second, the teaching of reading; the third, the methodological paths that have been adopted; and the fourth, the data analysis that took the reading strategies of experienced readers as categories.